SOCIAL PROFILE AND FUNCTIONAL FITNESS FOR ELDERLY RESIDENTS IN THE UNICIPALITY OF TRIUMFO – PE (Fiep Bulletin - online, 2016)
INTRODUCTION:The Brazilian population is aging at an accelerated pace. The significant increase in the number of elderly in the population makes it important to consider the phenomenon of aging from different perspectives. The natural aging process of human life brings with it numerous motor, metabolic and psychological changes, these changes directly affect the style and quality of life. OBJECTIVE: Draw the functional profile of the elderly in the city of Triunfo-PE; Assess the functional capacity of the elderly aged over 60 years; Identify the level of functional independence of the elderly; Propose strategies for intervention program through physical activity. METHODOLOGY:51 patients of both sexes, aged over 60 years were evaluated. The seniors had their functional capacity assessed through the battery of tests containing Fullerton: BMI, sitting and standing in 30 seconds, biceps Thread 30 seconds, touching hands behind his back, Sit and Reach, Time Up and Go, march stationary 2 minutes . RESULTS AND DISCURTIONS: The age groups studied were of 60-84 years old. Through history it was possible to identify the social issues of the elderly people. Following analyze the profile of the functional abilities of the elderly people through the battery of Fullerton where test were classified as; poor, fair, average, good and excellent agreement with the ratios obtained. CONCLUSION: The study revealed an elderly population with predominantly female majority in the age group 65-69 years old, with low education level. The data indicates the need for an intervention program on health issues through physical activity due to social characteristics indicated must have a character of gratuity in order to combat the deleterious effects of the aging process thus improving the quality of life.
Keywords: functional capacity; Elderly; Evaluation.